Di Balik Greenwashing: Kebenaran Tentang Keputusan Investasi - Dwi Asih Meilani; Siti Mutmainah (Owner : Riset dan Jurnal Akuntansi, 2025)
Many businesses engage in competitions to show dedication to sustainability, but a significant number engage in deceptive methods. We refer to this condition as greenwashing. The impact of greenwashing on companies investment choices is the intended focus of this research. During the years 2021-2023, the study’s sample included Indonesia Stock Exchange companies operating in the manufacturing industry. We employed a quantitative research method, utilizing linear regression. The findings disprove the hypothesis that greenwashing discourages investment by corporations. Greenwashing in manufacturing companies is not considered a significant indicator by investors. Neither ROE nor DER nor firm size, which are control variables, significantly affect investment choices. These findings demonstrate developing a more thorough comprehension of how investors evaluate business about sustainability. Even though greenwashing is not considered a significant signal, this does not mean that companies are free to ignore their contribution to social and environmental responsibility. Tangible and transparent sustainable practices can create reputation and investor confidence over time. Therefore, companies should prioritize true and measurable sustainability plans over marketing green claims that may not affect current investment decisions but may influence future views and decisions. On the other hand, CapEx is significantly and positively affected by ROA. A positive signal from ROA indicates that the business has strong financial prospects in increasing investor confidence.